Gambaran Kepuasan Hidup Pelajar Sekolah Menengah Di Masa Pandemi COVID-19 - Syamila, Diana; Handika, Mardy; Sari, Mariana Puspa (Ridwan Institute, 2021)
The purpose of this study is to find out the picture of life satisfaction of secondary school students during the Covid-19 pandemic based on the aspects outlined in the research questionnaire. The purpose of this study is to see a picture of student life satisfaction during the covid-19 pandemic. The research method uses descriptive quantitative withdata swearing techniques using Multidimensional Student's Life Satisfaction Scale (MSLSS) with 40 statement items. The number of samples in this study was 125 people with the sample technique used is probability sampling. In the presayarat test analysis using kolmogrov-smirnov and lilliefors using SPSS microsoft for windows versi 25 showed a value of test statistic 0.762 > 0.05 and sig. Lilliefors 0.606 > 0.05 is declared normal distributeddata. Based on hasil research obtained the results of sangat tinggi as much as 5% (6 learners), category tinggi as much as 34% (42 learners), category cukup as much as 41% (51 learners), category rendah as much as 13% (17 learners), and category sangat rendah as much as 7% (9 learners) on the life satisfactionof adolescent learners in the mas a pandemicCOVID-19. So it can be said that overall students of SMP Muhammadiyah 16 Jakarta, MTs Kafila Jakarta, and SMP Global Islamic School Jakarta; havea goodlife satisfaction,this indicates that in the covid-19 pandemic that experienced a change in the situation and limited access in various aspects of life, students are still able to survive and adapt.